Growth Mindset dan Grit pada Pimpinan Cabang Muhammadiyah - Wahidah, Fatin RN; Wibowo, Ugung DA; Gunawan, Gunawan; Luthfiyanti, Intan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The leaders of Muhammadiyah in branches are the key persons of Muhammadiyah who must be grit in maintaining, developing, and raising Muhammadiyah as the driving force of the Muhammadiyah organization. One of the factors that influence grit is the growth mindset. This study examines the effect of a growth mindset on the grit of Muhammadiyah leaders in branches. The sample is Muhammadiyah leaders in branches from the Purbalingga and Banyumas areas (N=37), taken using convenience sampling. This study uses a quantitative approach by deploying a modified grit scale from Duckworth's theory (2016) and a growth mindset scale adapted from Chen (2021). The results showed no effect of a growth mindset on grit (p>0.05). It is estimated that other factors influence the tenacity of Muhammadiyah leaders. Further discussion is discussed in this study.